التصميم الاقتصادي الأمثل لأقطار الأنابيب المستخدمة في أنظمة الري بالرش المضغوطة باستخدامVisual Basic (6.0) - عمار, سلاف (Latakia University Journal -Biological Sciences Series, 2016)
إن المشكلة الرئيسة التي تواجه المصمم هي اختيار مخطط تصميم النظام، والذي يعتمد على عدة عوامل: أحد هذه العوامل هو تحديد الضياعات الاحتكاكية الإجمالية للأنابيب، والتي تؤثر بشكل رئيسي ليس فقط على الأنابيب، ولكن على المضخة أيضا". العامل الثاني هو تحديد التكلفة الكلية لخطوط الأنابيب التي تؤثر بشكل رئيسي على التكلفة الإجمالية للنظام. إن الغاية من هذه الدراسة هو الحصول على قيمة القطر الاقتصادي للأنبوب بأقل تكلفة، والحفاظ على الضغط في كل نقط شبكة الأنابيب، لتعطي انسيابية مناسبة لكل الرشاشات. وقد كتبت النتائج بشكل تفصيلي بحيث وجدنا المعيار التالي: عندما يكون التدفق نفسه في أنابيب عدة مع الاختلاف في أطوال هذه الأنابيب ستكون قيمة قطر الأنبوب وقيم التكاليف هي نفسها لهذه الأنابيب. مع العلم أن قيمة الضياعات ستكون أكبر للأنبوب الأطول. The main problem facing the designer is the choice of optimum system layout, which depends on several factors. One of these factors is the assessment of total friction losses of the pipes, which mainly affects not only the pipe but also the pump. The second factor is assessment of capital cost of pipelines, which mainly affects the total cost of the system. The aim of this study is getting less cost of pipes and keeping the pressure in all points of pipes net to give suitable flow to all sprinklers. The results have been written analytically and we have found the following standard: When the flow is the same in several pipes and the difference is the length of these pipes, the value of pipe's diameter and the values of costs will be the same for these pipes. Nevertheless, the value of head loss will be biggest for the longest pipe.